Revitalizing Buya Hamka's Integration of Faith and Morals as an Effort to Rehumanize Modern Education - Lalita Ni'mal Fajria; Muhammad Fahmi (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This research aims to revitalize Buya Hamka's integration of faith and morals in rebuilding the concept of humanization in modern education. This study stems from concerns about the moral crisis and dehumanization in the education system, which overemphasizes cognitive aspects and neglects spiritual character formation. The research method used is a qualitative approach with library research, through hermeneutic analysis of Hamka's key works, such as Tafsir al-Azhar, Lembaga Budi, Falsafah Hidup, and Sufism Modern. The results show that Hamka viewed faith and morals as two inseparable elements: faith serves as a spiritual foundation, while morals are a concrete reflection of living faith. This integration creates an educational paradigm that balances intellectual, moral, and spiritual aspects. The implication is that the education system needs to be directed towards the formation of the whole person (insan kamil) through synergy between the family, school, and community. This study confirms the relevance of Hamka's thought in the context of contemporary education, which faces the challenges of globalization and a values crisis. Furthermore, it enriches the theoretical discourse on Islamic education by offering a new conceptual framework based on faith and morality as a foundation for the rehumanization of education.